Assistance in Financial Reporting for Micro, Small, and Medium Enterprises (MSMEs): A Case Study of Frozen Food Segara Biru in South Tambun District - Yusril Yusril; Jarkoni Jarkoni; Yustiar Cindy Audina (Doctoral Program of Social Science, Pasundan University, 2023)
Micro, small, and medium enterprises (MSMEs) play a crucial role in the local economy, including in the South Tambun District. However, MSMEs often face challenges in accurate and effective financial reporting. The lack of understanding of important aspects of financial reporting can hinder the growth and sustainability of their businesses. This activity aims to provide assistance and development in financial reporting to Frozen Food Segara Biru, an MSME located in the South Tambun District. In this assistance program, we collaborate with the business owners and their financial staff to enhance their understanding and skills in transaction recording, financial statement preparation, financial performance analysis, and sound financial management strategies. The methodology used is a collaborative approach, where we involve the business owners and financial staff in every step of the assistance process. We provide training and guidance on the concepts and practices of good financial reporting, as well as practical guidance on the use of accounting software or cloud-based applications to facilitate financial recording and reporting. It is expected that the results of this assistance will enhance the understanding and financial reporting skills of Frozen Food Segara Biru, which, in turn, will assist them in making better business decisions, improving operational efficiency, and accessing better financial resources such as loans or investments. Through this research, we hope to provide new insights into the importance of assistance and development in financial reporting for MSMEs, as well as offer practical recommendations for further development in this area. By supporting MSMEs in improving their financial reporting practices, we contribute to their overall growth and contribute to the local economy's development.